The Effect Of Service Quality And Academic Information System Quality On Student Satisfaction At The Faculty Of Economics And Business, Dehasen University Bengkulu - Irwandi, Abdurrahman; Anggriani, Ida; E G, Ida Ayu Made (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to determine the effect of service quality and academic information system quality, both partially and simultaneously, on student satisfaction at the Faculty of Economics and Business, University of Dehasen Bengkulu. This research uses a quantitative descriptive-associative approach with a survey method. The sample consisted of 97 student respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using SPSS version 25, through validity testing, reliability testing, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R2). The results show that service quality (X1) has a regression coefficient of 0.060, with a t-value of 1.302 and a significance value of 0.196 (> 0.05), indicating a positive but not significant effect on student satisfaction. Meanwhile, academic information system quality (X2) has a regression coefficient of 0.535, with a t-value of 12.256 and a significance value of 0.000 (< 0.05), indicating a positive and significant effect on student satisfaction. Simultaneously, the F-test result shows an F-value of 308.669 with a significance value of 0.000 (< 0.05), meaning that both variables together have a significant effect on student satisfaction. The coefficient of determination (R2) of 0.868 indicates that 86.8% of the variation in student satisfaction is explained by service quality and academic information system quality, while 13.2% is influenced by other factors outside this study.